Regression of Plaque Enhancement Within Symptomatic Middle Cerebral Artery Atherosclerosis: A High-Resolution MRI Study - Yang, Wen-Jie; Abrigo, Jill; Soo, Yannie Oi-Yan; Wong, Simon; Wong, Ka-Sing; Leung, Thomas Wai-Hong; Chu, Winnie Chiu-Wing; Chen, Xiang-Yan (Frontiers in Neurology, 2020)
Objective Contrast enhancement is a vital feature of the intracranial atherosclerotic plaque on high-resolution magnetic resonance imaging (HRMRI), but its clinical significance is still unclear. We aimed to quantitatively assess the plaque enhancement patterns in the middle cerebral artery (MCA) atherosclerotic plaque. Methods We conducted a cross-sectional study by prospectively recruiting stroke or transient ischemic attack patients with >30% of MCA stenosis of either side. All patients underwent contrast-enhanced HRMRI scans. Enrolled patients were classified into acute phase (<4 weeks), subacute phase (4-12 weeks) and chronic phase (>12 weeks) groups based on the time interval from stroke onset to imaging scan. The plaque enhancement index was calculated for each MCA lesion at the maximal narrowing site. Results We identified a total of 89 MCA plaques [53 (60%) symptomatic and 36 (40%) asymptomatic; 57 (64%) acute, 18 (20%) subacute and 14 (16%) chronic] in 58 patients on HRMRI. Among the acute lesions, symptomatic plaques had a significantly stronger plaque enhancement than asymptomatic plaques (symptomatic vs. asymptomatic: 38.9 ± 18.2 vs. 18.2 ± 16.2, p<0.001). Among the symptomatic lesions, plaque enhancement diminished with increasing time after stroke onset (38.9 ± 18.2, 22.0 ± 22.8, and 5.0 ± 10.1 for acute, subacute, and chronic phase, respectively; p for trend =0.001). Conclusion Plaque enhancement in the acute atherosclerotic plaque is closely related to recent ischemic events. In symptomatic atherosclerosis, plaque enhancement regresses over time after ischemic stroke, which may offer the potential to monitor the plaque activity in intracranial atherosclerosis using HRMRI.